Recycling of Organic Wastes for Substitution of Nitrogen and Maintenance of Soil Fertility - Tomar, V.P.S.; Dadhwal, K.S.; Narain, P.; Singh, J.P. (Indian Journal of Agroforestry, 2020)
A field study on nitrogen substitution through organic materials of multipurpose tree species(MPTS) was conducted at Research Farm, Selakui of Central Soil and Water Conservation Research and Training Institute, Dehradun from 1992 to 1995 to see the effect on soil moisture status and crop yield. The soil of study site was a silty loam acidic (pH 5.6, PWP 11.4, FC 25.6 and QC 0.45%). Six levels of nitrogen (20, 40, 60, 80 and 120 kg N/ha) were applied through urea, Leucaena leucocephala, Pueraria hirsuta and Shorea robusta having one control treatment. These organic materials were incorporated in soil one month before sowing of wheat every year and residual effect was seen on maize crop. At various crop growth stages L. leucocephala and P hirsuta conserve more moisture provided to wheat crop upto 0-30 cm depth. All the organic materials slightly lowered the pH by improving QC, available N, P & K at higher levels (100 and 120 kg/ha). All levels of nitrogen through different organic materials and urea increased grain yield of wheat. The highest grain yield of 32.6 q/ha was obtained with 100 kg N/ha through urea followed by L. leucocephala and P hirsuta. This study revealed that for rainfed wheat In north-west Himalayan region, N can be substituted from organic materials @ 100 kg/ha by Leucaena leucocephala and Pueraria hirsuta which in turn not only provided higher grain and straw yields but also ameliorated soil characterstics.